The Lipid-Lowering Effect of Dietary Taurine in Orange-Spotted Groupers (Epinephelus coioides) Involves Both Bile Acids and Lipid Metabolism - Wang, Xuexi; Bai, Fakai; Niu, Xingjian; Sun, Yunzhang; Ye, Jidan (Frontiers in Marine Science, 2022)
An 8-week feeding trial was conducted to investigate how dietary taurine supplementation attenuate the lipid deposition induced by dietary high lipid in juvenile orange-spotted grouper (Epinephelus coioides). Three isonitrogenous (47% crude protein) semi-purified diets were formulated to contain two levels of lipid and termed as 10% lipid diet, 15% lipid diet and 15% lipid with 1% taurine (namely, diet 10L, diet 15L and diet 15L+T, respectively). Groupers fed diet 15L+T showed higher weight gain and feed efficiency compared with diet 15L. Groupers fed diet 15L showed higher liver lipid contents, plasma total cholesterol (TC) and leptin contents vs those fed diet 10L. Diet 15L+T decreased hepatosomatic index, liver lipid content and plasma TC and adiponectin contents, and increased liver 3-hydroxy-3-methy1 glutary1 coenzyme A reductase content compared with diet 15L. Fish fed diet 15L had higher contents of chenodeoxycholic acid, deoxycholic acid and lithocholic acid, and lower contents of glycodeoxycholic acid (GDCA), glycolithocholic acid, glycoursodeoxycholic acid, taurodeoxycholic acid (TDCA), β-, γ- and ω-muricholic acid (MCA) when compared with fish fed diet 10L. Diet 15L+T down regulated the contents of glycocholic acid, glycochenodeoxycholic acid, taurohyodeoxycholic acid, tauromuricholic acid, TDCA, ursodeoxycholic acid, GDCA, and β-MCA vs diet 15L. Diet 15L up-regulated expression of peroxisome proliferator activated receptor α (pparα) gene, but down-regulated expression of acyl-CoA carboxylase (acc), fatty acid synthase (fas) and glucose-6-phosphate dehydrogenase (g6pd) genes in comparison with diet 10L. The gene expression level of fas and 6pgd was down-regulated and pparα gene expression level was up-regulated in fish fed diet 15L+T compared with those in fish fed diet 15L. Overall, the present study indicated that dietary taurine supplementation can attenuate the liver lipid deposition of groupers caused by feeding 15% lipid through accelerating lipid absorption of taurine-conjugated bile acids and fatty acid β-oxidation, and inhibiting lipogenesis.